TANTANGAN GURU DALAM IMPLEMENTASI PEMBELAJARAN TEMATIK DI SDN KUIN UTARA 5 BANJARMASIN - Ramdhani, Susanty; Utami, Cici Syifa; Mailani, Eka Maulida; Pratiwi, Diani Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to analyze the implementation of thematic learning in the Merdeka Curriculum at elementary schools. This research employs a qualitative method with data collection techniques, including interviews, questionnaires, and document analysis. The study involved five teachers as respondents. The findings reveal that most teachers possess adequate understanding and experience in designing thematic learning topics, preparing Thematic Lesson Plans (RPP), and integrating local wisdom values into the learning process. However, the main challenges faced by teachers include difficulties in integrating Basic Competencies (KD) across certain subjects and technical constraints, such as limited time and supporting resources. Thematic learning is considered effective, especially for lower-grade students, as it provides concrete and interactive learning experiences. In conclusion, thematic learning within the Merdeka Curriculum enhances the quality of education, though increased resource support and continuous teacher training are necessary. Keywords: Thematic Learning, Merdeka Curriculum, Local Wisdom